A rare case of ovarian hemangioma in a 30-year-old nulligravid woman - Harry Ramos, BS, BA; Nithin Thummala, MD; Suzanne M. Jacques, MD; Radhika Gogoi, MD, PhD (Radiology Case Reports, 2023)
A 30-year-old nulligravid woman with a history of polycystic ovarian syndrome presented for evaluation of left adnexal mass. The patient was referred to the gynecologic oncology clinic after endorsing signs of abdominal pain for a month and the pelvis ultrasound demonstrated hypoechoic solid mass in the left ovary. Magnetic resonance imaging with T1- and T2-weighted images demonstrated progressive centripetal “filling-in” of the mass suggesting a unique variation of malignant ovarian mass, similar to what is seen in hepatic hemangioma. Upon resection of the ovarian mass, pathology reported that the mass was filled with numerous small blood vessels with single later of endothelial cells confirming the diagnosis of ovarian hemangioma, capillary-type—a rare finding.